Providence Their Guide - Naudé, A.D. (Scientia Militaria - South African Journal of Military Studies, 2011)
In his preface to this book the author quotes from Milton's Paradise lost, from which the title of this book is derived: 'Som natural tears they drop'd, but wip'd them soon; The World was all before them, where to choose Thir place of rest, and Providence thir guide; They hand in hand, with wand ring steps and slow, Through Eden took thir solitarie way.